Interventions for Frequently Hospitalized Patients and Their Effect on Outcomes: A Systematic Review. Issue 12 (31st October 2018) - Goodwin, Alexandra; Henschen, Bruce L.; O'Dwyer, Linda C.; Nichols, Natasha; O'Leary, Kevin J.
Abstract : BACKGROUND: A small subset of patients account for a substantial proportion of hospital readmissions. Programs to reduce utilization among this subset of frequently hospitalized patients have the potential to improve health and reduce unnecessary spending. PURPOSE: To conduct a systematic review of interventions targeting frequently hospitalized patients. DATA SOURCES: PubMed MEDLINE; Embase (embase. com); and Cochrane Central Register of Controlled Trials, January 1, 1980 to January 1, 2018. STUDY SELECTION: Four physicians screened 4762 titles and abstracts for inclusion. Authors reviewed 116 full‐text studies and included 9 meeting criteria. DATA EXTRACTION: Study characteristics, outcomes, and details regarding interventions were extracted. Risk of bias was assessed by the Downs and Black Scale. DATA SYNTHESIS: Out of the nine included studies, three were randomized controlled trials, three were controlled retrospective cohort studies, and three were uncontrolled pre‐post studies. Inclusion criteria, interventions used, and outcomes assessed varied across studies. While all nine studies demonstrated reduced utilization, studies with lower risk of bias generally found similar reductions in utilization between intervention and control groups. Interventions commonly consisted of interdisciplinary teams interacting with patients across health care settings. CONCLUSIONS: Interventions targeting high need, high‐cost patients are heterogeneous, with many studies observing a regression to the mean. More rigorous studies, using multifaceted interventions which can adapt to patients' unique needs should be conducted to assess the effect on outcomes relevant to both providers and patients.